Terra Firma et Novum Regnum Granatense et Popayan - Blaeu, Willem Janszoon, 1571-1638 (Blaeu, Willem Janszoon, 1571-1638, 1631)
Shows Central America and northwestern South America. Relief shown pictorially. Dutch text on verso page 13. Signature: L. Gift of Pat Van Alyea. This map of 1631 by Willem Janszoon Blaeu (1571–1638) shows Central America and the northwestern part of South America, including all or parts of Colombia, Ecuador, and Venezuela. A Dutch text on the reverse of the map explains the geography of the regions depicted, which encompassed the Spanish viceroyalty of New Granada and the province of Popayán, which took its name from the colonial city located at the foot of Volcán Puracé in the Cordillera Central of the Andes. The map shows rivers and other geographic features, along with towns and missions. Relief is shown pictorially. The map has two distance scales, Spanish leagues and German miles. Blaeu places a hand-colored compass rose in the Caribbean Sea (labeled the Northern Ocean, the term for the Atlantic in use at the time), and another, slightly larger one in the Pacific (labeled the Southern Ocean). The title, scales, Blaeu’s signature, and other information on the map are in Latin, but place-names are in Spanish. Blaeu was a leading Dutch cartographer and map publisher and the founder of a family of distinguished mapmakers that included his sons Joan and Cornelis. Born in the Netherlands in 1571, between 1594 and 1596 Blaeu studied in Denmark under the astronomer Tycho Brahe, where he developed skills as an instrument and globe maker. Upon returning to Amsterdam, he founded the family map company. In 1608 he was appointed chief hydrographer of the Vereenigde Oost-Indische Compagnie (United East Indian Company), a position he held until his death. The use of the compass rose and the careful marking of capes, islands, and shallows along the coasts reflect his interest in marine cartography. WDL Color 1:4,000,000